Effectiveness of various treatment strategies in COVID-19 patients having Solid Organ Transplant: A Systematic Review - Muhammad Shehryar Hussain , Khadeja Farrukh , Tehniyat Iqbal , Aleeza Fatima , Zunira Mughis , Hafiz Amjad Hussain (Journal of Rawalpindi Medical College, 2021)
Introduction: This narrative review provides an evidence-based summary of the various interventions in the management of Post Solid organ transplant patients who reported positive for COVID-19. Materials and Methods: For this systematic review, observational and experimental studies; conducted on Post- Organ transplant patients, either symptomatic or asymptomatic, who tested positive for COVID-19 were included. Only solid organ transplant patient studies were considered standard for this review type. The English version, both published and unpublished articles, from Dec 2019 to Aug 2020, were evaluated using Pubmed, Google Scholar, Science direct, Medrixv search engines. The articles with incomplete details about a transplant or covid management were excluded. Results: We selected 43 articles out of which 9 were retrospective studies, 2 were cohort studies, one was an experimental study, and 31 were case studies. According to the literature review, effective management therapy includes the withdrawal of immunosuppressive drugs, increase/ constant steroid dose, and regimen containing HCQ, interleukin inhibitor, and one antiviral drug especially remdesivir proved to be the most effective among all. In others, administration of IV immunoglobulins/convalescent plasma therapy proved effective in various trials but related data is currently limited. While Lop/Rit, Interferons alpha, and oseltamivir trials are also given; these therapies didn’t prove to be much effective individually. Conclusion: More trials are required to find the effectiveness of Convalescent plasma therapy. It can be proved as an effective treatment in critical patients. IV immunoglobulins effectiveness should also be tested in critical patients and for this more experimental trials are needed.